Essential Oil of Thottea grandiflora and its Lipoxygenase Inhibitory Activity (SCOPUS) - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2021)
Essential Oil of Thottea grandiflora and its Lipoxygenase Inhibitory Activity (SCOPUS) by Wan Mohd Nuzul Hakimi Wan Salleh